(3QSGFd GdNWjH GdMUcais - (3GdMUcaj , jMji Hf SdGeI Hf GdMSjf, eYjf GdOjf CHh GdaVd,J (B551 (3g` s ((3eMeO GHQGgje s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOGjhGaj fYeghHYO agPG eG LQi Hg bde GdGeGe GdHGQYef gPg GdefTFGJ GdHOGFY, heG MOK aj GdCdaGX GdQhGFY s
(3BNQgG (B:s
(3acOQJg GddjGdj hGi YjT jOhe gPG eG hLOfGg ef fKQg GdQGFb hfXeg GdZGFb s
(3HGdeYgO fSNI CNQi JMJ Qbe (B420 (3GOHs
(3GdLRA GdChds
(3cJHgG GdfGSN ef fSNI ecJhHI HGdcJHNGfI GdeUQjI GdNOjhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B18 s
Keywords: (3GdCOHs